Oxford think! new syllabus Mathmatics 1 - Har, Dr Yeap Ban (Karachi : Oxford university press, 2024)
"Think! New Syllabus Mathematics 1 (8th Edition)" is a comprehensive mathematics textbook designed for middle school students. This book introduces foundational concepts in mathematics, following a structured and progressive approach that aligns with the syllabus requirements. It aims to help students develop strong mathematical skills while engaging them in active learning.
Keywords: Math : Textbook; Oxford : 8th edition